Anthelmintic resistance in livestock in Africa: review of the current status - Gatitu, Lucy; Kasudi, Mitchelle R.; Githigia, S.; Moodley, Arshnee; Muloi, Dishon M. (BioMed Central, 2025)
Background: Livestock across the globe are frequently infected with multiple gastrointestinal nematode (GIN) species, and the use of anthelmintics remains a cornerstone of their control. However, anthelmintic resistance (AHR) poses a growing threat to sustainable livestock production, resulting in reduced productivity and compromised animal health and welfare. Reports of resistance in various helminth species against multiple anthelmintic classes exist in African livestock; however, studies summarising the extent and burden of this resistance are limited, and systematic monitoring or surveillance efforts are largely absent across the continent.